The trainer's handbook - Lawson, Karen (Pfeiffer, 2006)
This thoroughly revised and updated second edition of The Trainer’s Handbook presents a comprehensive, systematic approach to developing training skills and competencies. It reflects the current changes in the design, development, and delivery of training that will meet the needs of today’s learner, distance learning, and performance consulting. The book offers a fresh focus on evaluation, includes practical how-to guidance, and a wealth of illustrative real-life examples.